Photovoltaic energy rating data sets for Europe. (August 2016) - Huld, Thomas; Salis, Elena; Pozza, Alberto; Herrmann, Werner; Müllejans, Harald
Highlights: We present a study of the variability of PV performance in Europe. Sensitivity analysis of PV module measurements show about 2% uncertainty in module performance ratio. Based on the performance maps and the uncertainty in PV module measurements we propose 4 climatic data sets for energy rating. Abstract: We present a study of possible climatic data sets that can be used to perform energy rating calculations on photovoltaic (PV) modules in Europe. We selected five geographic locations across Europe to cover the range of climatic conditions present. In order to assess the validity and significance of such climatic data sets we performed a detailed analysis of the sensitivity of the calculated energy rating to the variability of the input parameters. These are the transmission of the front glass based on the angle of incidence of the irradiance, the spectral response measurement of the PV module, coefficients for calculating module temperature from ambient temperature, and measured power matrices as function of module temperature and irradiance. We found that the calculated energy rating is not sensitive to the first three, but mainly varies due to difference in measured power matrices. This is in particular true for the module performance at low irradiance, and therefore shows a more pronounced difference in climates where such low irradiance conditions occur more frequently, such as in the northern parts of Europe. Nevertheless, the variability found is still less than those between geographic locations. We propose a selection of four energy rating data sets, which differ between them by more than the uncertainty and represent the main climates present across Europe.